2014
DOI: 10.4172/1747-0862.1000096
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Problems with Viral Vectors for Delivery of Talens

Abstract: Transcription Activator-Like Effector Nucleases (TALENS) and Their Mode of ActionFor sequence-specific genome engineering and its biotechnological and medical applications various systems were tested. Most recent tools include designer nucleases and the bacteria derived clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 system using short RNA to induce precise cleavage at endogenous genomic loci [1,2]. Designer nucleases are mainly represented by zinc finger nucleases (ZFNs) and transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…31 In other words, TALE repeats can target longer sequences of interest. 32 33 is noteworthy. Overall, the aforementioned problems limit the applications of TALENs, and further research is required to resolve these issues ( Table 1).…”
Section: Transcription Activator-like Effector Nucleasementioning
confidence: 97%
See 1 more Smart Citation
“…31 In other words, TALE repeats can target longer sequences of interest. 32 33 is noteworthy. Overall, the aforementioned problems limit the applications of TALENs, and further research is required to resolve these issues ( Table 1).…”
Section: Transcription Activator-like Effector Nucleasementioning
confidence: 97%
“…Previous studies conducted with the aim of overcoming these problems revealed that the number of repeats has a direct relationship with specificity in TALENs and, in addition, attempts to join two TALEN expression cassettes with the aim of improving efficiency using vector systems such as adeno‐associated virus (AAV), lentivirus and adenovirus would be unsuccessful. Of the efforts made to resolve this issue, the use of internal ribosomal entry sites (IRES) or A2 peptides in the design of vectors is noteworthy. Overall, the aforementioned problems limit the applications of TALENs, and further research is required to resolve these issues (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…TALENs function similarly to ZFN, but possess dramatically improved specificity. There have been several reports demonstrating successful applications in hESCs/hiPSCs [5456], however, TALENs also are subjected to the same concerns as ZFNs in that their delivery is mostly dependent on viral transduction [57], there is a high rate of non-specific targeting that may result in tumorigenesis (even if the intended target is a safe harbor site) [58], and validation can be laborious.…”
Section: The New Frontier: Using Gene-corrected Pluripotent Stem Cellmentioning
confidence: 99%
“…Because the size of the AAV vector genome is limited to less than ~4.7 kb, it is difficult for the vector to hold the spCas9 or TALEN gene. Consequently, two viruses are required for TALEN delivery, one for the right part and one for a left part of TALEN . In addition to the delivery of the intact enzymes, introduction of control elements to customize expression in the system is also being considered.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, two viruses are required for TALEN delivery, one for the right part and one for a left part of TALEN. 8 In addition to the delivery of the intact enzymes, introduction of control elements to customize expression in the system is also being considered. This makes the physical size limit an even more serious problem.…”
Section: Introductionmentioning
confidence: 99%